얼굴표정에서 나타나는 감정표현에 대한 어린이의 반응분석 - 유동관(Dong-Kwan Yoo) (한국콘텐츠학회 논문지, 13(12), 2013)
The purpose of this study has placed its meaning in the use as the basic material for the research of the person's facial expressions, by researching and analyzing the visual reactions of recognition of children according to the facial expressions of emotion and by surveying the verbal reactions of boys and girls according to the individual expressions of emotion. The subjects of this study were 108 children at the age of 6 - 8 (55 males, 53 females) who were able to understand the presented research tool, and the response survey conducted twice were used in the method of data collection by individual interviews and self administered questionnaires. The research tool using in the questionnaires were classified into 6 types of joy, sadness, anger, surprise, disgust, and fear which could derive the specific and accurate responses. Regarding children's visual reactions of recognition, both of boys and girls showed the high frequency in the facial expressions of joy, sadness, anger, surprise, and the low frequency in fear, disgust. Regarding verbal reactions, it showed the high frequency in the heuristic responses either to explore or the responds to the impressive parts reminiscent to the facial appearances in all the joy, sadness, anger, surprise, disgust, fear. And it came out that the imaginary responses created new stories reminiscent to the facial expression in surprise, disgust, and fear. 본 연구의 목적은 열굴 표정의 감정표현에 따른 어린이의 시각적 인지반응을 연구, 분석하고 각각의 감정표현에서 나타나는 남녀어린이의 언어적 반응을 살펴봄으로써 인물표정연구의 기초자료로 활용되는데 그 의미를 두었다. 연구대상은 제시된 연구도구를 이해할 수 있는 6~8세 어린이 108명(남 55명, 여53명)으로 하였으며, 2차에 걸쳐 실시한 반응조사는 어린이의 개별면접과 자기기입식 설문지를 통한 자료수집방식을 활용하였다. 설문에 활용한 연구도구는 남녀어린이의 구체적이고 정확한 반응을 도출할 수 있는 기쁨, 슬픔, 화남, 놀람, 혐오감, 공포감 등 6가지 유형으로 구분하였다. 어린이의 시각적 인지반응결과에서 남녀어린이 모두 기쁨, 슬픔, 화남, 놀란 표정에 대한 빈도수가 높게 나타났으며, 공포감과 혐오감을 느끼는 얼굴표정에 대한 빈도수는 남녀어린이 모두 낮게 나타났다. 언어적 반응은 기쁨, 슬픔, 화남, 놀람, 혐오감, 공포감 모두 얼굴표정에서 연상되는 인상적인 부분을 찾아 대답하거나 얼굴표정의 시각적 특징을 기초로 추론하거나 탐구하는 발견적 반응이 높게 나타났으며, 놀람과 혐오감, 공포감에서 얼굴표정을 보고 연상되는 새로운 이야기를 만들어 내는 상상적 반응이 나타났다.